KEEFEKTIFAN PEMBELAJARAN MATEMATIKA BERBASIS SMART DENGAN STRATEGI TAI PADA MATERI SEGITIGA KELAS VII - Aryo Andri Nugroho (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Abstract  This study is aimed to increase the students’ achievement in learning mathematics on grade VII SMP Islam Pekalongan using SMART-Based Mathematics Learning by  TAI  Strategy.  It  is  a  Queasy  Experimental  model.  The  population  is  the students  of  grade  VII  SMP  Islam  Pekalongan  that  consists  of  eight  classes.  The writer  uses  the  random  sampling  to  choose  the  samples;  there  are  two  classes, class  VII  1  as  the  experimental  class  and  class  VII  2  as  the  control  class.  The variables  are  the  students’  activeness  (X1)  and  skill  process  (X2)  as  the independent  variables,  meanwhile  the  students’  achievement  (Y)  is  as  dependent variable.  The  methods  of  collecting  data  are  by  observation  and  learning achievement  test.    The  data  analyses  are  by  comparison  and  influence  test.  The result  of  this  study  shows  that  the  students’  achievement  is  77,59.  It  means  that the students’ achievement is good. There is a difference between the experimental and  control  class.  The  variables  of  students’  activeness  and  skill  process  have positive  influences on the students’ achievement with  the regression  y^= -33,964 +  1,003  X1  +  0,434  X2  and  the  influence  is  as  much  as  39%.  That  shows  the experimental class learning is effective.    Keywords: SMART, TAI, Cooperative Learning